Comparative pharmacokinetics and bioavailability of two tylosin formulations in chickens after oral administration - ABU-BASHA, EHAB A; AL-SHUNNAQ, AHMAD F.; GEHRING, RONETTE (Journal of the Hellenic Veterinary Medical Society, 2017)
The pharmacokinetics and oral bioavailability of two tylosin formulations was carried out in broiler chickens according to a single dose, randomized, parallel design. The two formulations of tylosin (Tylosina® and Tylan®) were given orally at a dose level of 25 mg/kg b.w. after an overnight fasting (n=15 chicken/group). To calculate tylosin bioavailability, fifteen more chickens was assigned as group 3 and was given a single intravenous dose of tylosin (25 mg/kg b.w.). Serial blood samples were collected at different time points up to 24 hour post-drug administration. A high performance liquid chromatography (HPLC) method was used for the determination of tylosin concentrations in chicken plasma. The pharmacokinetics analysis of the data was performed using non-compartmental analysis based on statistical moment theory with the help of commercially available software (WinNonlin®, Pharsight Corporation, Cary, NC, USA). There were no significant differences in the Cmax (3.05±0.63, 2.63±0.74 μg/ml), tmax (2.36±0.42, 2.30±0.38 h), t1/2β (1.99±0.38, 2.67±0.60 h), AUC0-12h (6.11±0.97, 5.37±1.16 μg.h/ml), AUC0-∞ (6.38±0.94, 5.57±1.15 μg.h/ml), MRT (3.53±0.24, 3.67±0.32 h), ClB/F (90.59±13.81, 169.38±54.44 ml/min/kg) and Vdz/F (16.85±4.74, 43.96±18.24 l/kg) between Tylosina® and Tylan®, respectively. The calculated oral bioavailability (F) for Tylosina® and Tylan® were 40.56 and 35.41%, respectively. Moreover, the relative bioavailability of Tylosina® was 113.9% when compared to Tylan®. In conclusion, Tylosina® is comparable to Tylan® and both formulations can be used for treatment of susceptible microorganisms in veterinary medicine practice at a dose level of 25 mg/kg b.w.